KESIAPAN INDUSTRI KECIL DAN MENENGAH DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Anna Widayani; Dwi Ariani Finda Yuniarti (STKIP PGRI SITUBONDO, 2021)
This study aims to determine the readiness of small and medium industries in facing the industrial revolution 4.0 in small and medium industries in the city of Blitar. This research uses a quantitative approach with this type of explanatory research. The number of samples in this study was 97 small and medium industry players in the food and beverage sub-sector in the city of Blitar. The results showed that the Average Variance Extracted (AVE) value for the Organizational Management variable is 0,767; People and Culture variable is 0,808; Product and Service variable is 0,705; Technology variable is 0,709 and the Factory Operation variable is 0,705. This means that these five variables have a positive and significant effect on the readiness of small and medium industries in facing the industrial revolution 4.0.